Fractional occupation numbers and self‐interaction correction‐scaling methods with the Fermi‐Löwdin orbital self‐interaction correction approach. Issue 12 (11th February 2020) - Aquino, Fredy W.; Shinde, Ravindra; Wong, Bryan M.
Abstract: We present a new assessment of the Fermi‐Löwdin orbital self‐interaction correction (FLO‐SIC) approach with an emphasis on its performance for predicting energies as a function of fractional occupation numbers (FONs) for various multielectron systems. Our approach is implemented in the massively parallelized NWChem quantum chemistry software package and has been benchmarked on the prediction of total energies, atomization energies, and ionization potentials of small molecules and relatively large aromatic systems. Within our study, we also derive an alternate expression for the FLO‐SIC energy gradient expressed in terms of gradients of the Fermi‐orbital eigenvalues and revisit how the FLO‐SIC methodology can be seen as a constrained unitary transformation of the canonical Kohn–Sham orbitals. Finally, we conclude with calculations of energies as a function of FONs using various SIC‐scaling methods to test the limits of the FLO‐SIC formalism on a variety of multielectron systems. We find that these relatively simple scaling methods do improve the prediction of total energies of atomic systems as well as enhance the accuracy of energies as a function of FONs for other multielectron chemical species. Abstract : The authors assess the performance of the Fermi‐Löwdin self‐interaction correction (FLO‐SIC) approach and simple SIC‐scaling methods for predicting energies as a function of fractional occupation numbers in various chemical systems.